PRAKTIK-PRAKTIK MANAJEMEN KINERJA PADA ORGANISASI SEKTOR PUBLIK DAN HUBUNGANYA DENGAN KINERJA ORGANISASI - Yuli Ariyadi; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2013)
The  study aims to investigate the effects of performance management practices in public sector organizations. The public sector organization that investigated in this study is government institutions of Republic Indonesia that managed APBN fund.This study was conducted by using questioner to the manager of the public sector organizations in Kota Bandung, Kabupaten Bandung, Kota Cimahi. The data obtained was processed by using PLS Aplication. The result of the study indicate that performance management practices in public sector organitation (clear and measurable goal) is positifically affected the public sector organization performance in quantity performance and quality performance. Insentif is positificaly affected the public sector organization performance in quantity performance but not yet effected quality performance.